CIVILIZATIONS CONCEPTS «RUSIIA», «STATE» AND «GOVERNOR» IN THE ART EXPRESSION OF RUSSIAN NATIONAL IDENTITY: SONNETS ON THE HISTORICAL SUBJECTS OF G.V. GOLOHVASTOV - A. V. Ostankovich; A. D. Fokina (Гуманитарные и юридические исследования)
The article is devoted to the concept sphere, including deep foundations of the Russian mentality in sonnets of Russian «American» G.V. Golohvastov.